Cardiac arrest following unopposed calcium replacement for cabozantinib-induced hypocalcaemia - Adithya Sreenivas; Dileep Jeewaka De Zoysa Hiddadura; Raghava Reddy (Clinical Medicine, 2025)
Introduction: Medullary thyroid carcinoma (MTC) is an aggressive form of differentiated thyroid cancer originating from calcitonin-producing parafollicular C cells, with well-established treatment guidelines, often including cabozantinib first-line.1 Cabozantinib is a tyrosine kinase inhibitor that specifically targets the MET, VEGFR2, and RET pathways, and is also utilised in renal cell carcinoma.2 While it is known to cause hypocalcaemia, we present an extremely rare event of hypercalcaemia-related cardiac arrest resulting from unopposed calcium and vitamin D metabolite supplementation following cessation of cabozantinib. Case presentation: A 47-year-old man with metastatic medullary thyroid carcinoma (MTC) presented to hospital with confusion and abdominal pain. The patient also reported cessation of cabozantinib for 3 weeks, while on holiday, and had recently completed a course of antibiotics for dental infection. On examination, he was febrile and tachycardic, with visible oral ulceration. His medical history included previous thyroidectomy, paroxysmal atrial fibrillation and supraventricular tachycardia requiring ablation.Admission blood tests demonstrated severe hypercalcaemia (serum corrected calcium 5.11 mmol/L (2.20–2.60)), raised C-reactive protein (CRP) of 183 mg/L (<10) and stage 3 acute kidney injury (AKI; serum creatinine 511 μmol/L (60–110), serum urea 25.3 mmol/L (2.5–7.0)). Computed tomography (CT) thorax, abdomen and pelvis was suggestive of possible development of bone metastasis. CT head and neck demonstrated no abnormality. His renal failure was suspected to be secondary to the hypercalcaemia. Admission electrocardiography (ECG) demonstrated sinus rhythm, with no QT prolongation.Pamidronate treatment was initiated, as well as intravenous fluid resuscitation and empirical antibiotic therapy for oral sepsis. Serum corrected calcium improved to 3.86 mmol/L and serum creatinine to 455 μmol/L. Despite this, he developed a cardiac arrest as an inpatient on Day 3 of admission, with return of spontaneous circulation after three defibrillator shocks. The patient was admitted to the intensive care unit for 1 week, with intubation and supportive management. Upon subsequent stepdown, he developed hypocalcaemia (serum corrected calcium 1.68 mmol/L), which required careful titration of alfacalcidol.During oncology follow-up, the following month, it was determined that palliative treatment with selpercatinib would be most appropriate, with twice-weekly serum calcium monitoring and monthly ECG. This was considering no structural changes demonstrated on echocardiogram. Discussion: Multikinase inhibitors are known to cause electrolyte disorders, with 10 cases of cabozantinib-related hypercalcaemia reported in a 2024 pharmacovigilance analysis in renal cell carcinoma patients.3 However, hypocalcaemia was reported at a much higher frequency, with 33 events in the same population. While the mechanism of hypocalcaemia is not fully understood for cabozantinib, the same study proposed that sorafenib may cause calcium mobilisation secondary to endoplasmic reticulum stress.Unopposed calcium-replacement therapy during cabozantinib was the most likely was of cardiac arrent in this case. A key differential was bone metastasis-related hypercalcaemia, although the resolution a short timeframe refutes this. Notably, no significant difference has been reported in rates of hypercalcaemia in patients treated with cabozantinib with and without bone metastases.4Patients may need to pause their antineoplastic treatment for a variety of reasons, including pre-operative cessation, severe haemorrhage (3%) and hypertensive crisis (18%).5 This case highlights the importance of patient counselling and regular monitoring, especially with respect to electrolyte supplementation in the context of chemotherapy agent use.